People competence assessment based on project management scenarios - Souza, Mariane Cásseres (2023)
Scenario-based assessment makes it possible to represent situations related to professional project management practices and, in this sense, allows the assessment of competences in contexts inspired by professional environments. From the point of view of project management competences, the Individual Competences Baseline (ICB) describes the competences required for individuals who work in the field. This framework shows, besides other competences, the 10 (ten) competences focused on people, namely: introspection and personal management; personal integrity and reliability; personal communication; leadership; teamwork; relationships and engagement; resourcefulness; conflict and crisis; negotiation and results orientation. This study aims to analyze the process of assessment of competences based on Project Management scenarios, in the context of the Engineering field. This study was based on an experimental process and involved Professors and Professionals in the Project Management area. As a result, an assessment of competences was obtained through dynamic, interactive scenarios, which promotes reflection and is aligned with professional project management practices. Another result points to the potentiality of applying scenarios, as a complementary strategy to traditional assessments. For future work, it is suggested to develop scenarios that can assess the other competences required by individuals who work in project management.